Mycobacterium tuberculosis lineages in Hawaii demonstrate distinctive demographic and migration characteristics. (May 2020) - Koster, K.; Largen, A.; Qian, L.; Sen-Crowe, B.; Douglas, J.T.
Abstract: Objectives: The American state of Hawaii presents a tuberculosis (TB) burden more consistent with that of the Philippines and the Pacific Islands than that with the United States (US) or Europe. This study seeks to determine if the genetic families of Mycobacterium tuberculosis ( Mtb ) that are prevalent in Hawaii display differences in host demographics that may be of use for TB control in Hawaii and the Pacific. Study design: This retrospective study was conducted by analyzing data from the Hawaii State Department of Health to investigate the demographics associated with the Beijing (global lineage 2) and Manila (lineage 1) families of Mtb in Hawaii. Methods: Deidentified records of all culture-positive TB cases reported by the Hawaii State Department of Health Tuberculosis Control Program from 2004 to 2016 were analyzed to identify lineage-specific demographic differences and trends. Patients' countries of origin, age, sex, and time in the US before TB diagnosis were included in this analysis. Results: Manila family isolates were found to predominantly enter Hawaii through Filipino immigrants, whereas Beijing family isolates originated from a diverse set of countries. Both families exhibited significant differences in age and sex demographics. In addition, Manila family cases presented from patients with significantly longer average time of residence in the US than non-Manila cases, whereas Beijing family cases presented from patients with significantly shorter time of residence in the US than non-Beijing cases. Conclusions: Both the Beijing and Manila families of Mtb demonstrated demographic differences in Hawaii that may prove important for improving TB control and surveillance policy in Hawaii and throughout the Pacific. Areas with heavy Filipino immigration may benefit from directing more resources toward screening and education efforts for middle-aged men and those who have resided in the country longer, whereas other areas of the Pacific should consider a younger and more sex-balanced allocation. Specific to the US and Hawaii, effective screening of youths emigrating from the Compact of Free Association states remains vital. Highlights: Hawaii's genetic lineages of Mycobacterium tuberculosis show distinct epidemiology. Beijing family cases in the Pacific originate from a diverse set of countries. Manila family TB is most common in older persons who have been in the USA longer. Beijing family TB has younger, diverse demographic and rapid disease presentation.